Effects of Photodynamic Therapy on the Adhesive Interface of Fiber Posts Cementation Protocols - Ramos, Anna Thereza Peroba Rezende [UNESP]; Garcia Belizário, Lauriê [UNESP]; Venção, Ana Carolina [UNESP]; Fagundes Jordão-Basso, Keren Cristina [UNESP]; de Souza Rastelli, Alessandra Nara [UNESP]; de Andrade, Marcelo Ferrarezi [UNESP]; Kuga, Milton Carlos [UNESP] (Elsevier, 2018)
Introduction The aim of this study was to evaluate the effects of photodynamic therapy (PDT) on the bond strength and dentinal penetrability of cementation protocols using conventional resin cement (Relyx ARC; 3M ESPE, St Paul, MN) or self-adhesive (Relyx U200, 3M ESPE) after the glass fiber post cementation. Methods Forty human canine roots were endodontically treated and prepared for a fiber post. The roots were divided into 4 groups according to the cementation protocol and PDT use: conventional cement (CC), Relyx ARC; self-adhesive cement (SAC), Relyx U200 cement; PDT/CC, PDT + Relyx ARC; and PDT/SAC, PDT + Relyx U200. After cementation of the fiber posts, the roots were cross sectioned, and then specimens from the cervical, middle, and apical thirds of the prosthetic space were obtained. The specimens were submitted to the pushout test and dentinal penetration evaluation of the cementation protocol using laser confocal microscopy. Results PDT/CC presented the lowest bond strength to root dentin in the cervical third (P <.05). In the middle and apical thirds, all groups presented a similar bond strength (P >.05). PDT/CC presented the lowest dentinal penetration of the adhesive system in the cervical and apical thirds (P <.05). Conclusions PDT presented negative effects on the bond strength to dentin in the cervical third after cementation using Relyx ARC and on the dentinal penetrability of the etch-and-rinse adhesive system in the cervical and apical thirds of the prosthetic space.
Keywords: Bond strength; fiber posts; photodynamic therapy; push-out bond strength; self-adhesive cement